Konstruksi Komunitas Kampus Terhadap Mahasiswi Bercadar Di Universitas Sriwijaya Indralaya - Puji Rahayu; Ridhah Taqwa (Jurnal Empirika, 2019)
This study examines the process of the formation of campus community construction of veiled female students by using a social construction approach from Peter L. Berger and Thomas Luckmann. The method used is qualitative with data collection techniques such as observation, interviews, and documentation. The research informants were selected purposively as many as eleven people, consisting of two lecturers, two employees, and seven students of Sriwijaya University. The results of this study indicate that the campus community construction of veiled female students can be known through three stages. First, externalisation is the process by which individuals in the campus community capture outside influences related to the use of the veil. Secondly, objectivation,Â  individuals in the campus community view the use of the veil as a form of respecting human rights. Third, internalisation takes the form of a subjective dimension of the campus community as meaning. Through primary and secondary socialisation, this study obtained four-campus community constructions of veiled female students, namely freedom in democracy, a form of servant obedience to God, religious bigotry, and violation of communication ethics.